THE INFLUENCE OF ORGANIZATIONAL CULTURE AND COMPETENCY ON THE DEVELOPMENT OF EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS A MEDIATION VARIABLE: PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP PENGEMBANGAN KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI - Putri Berutu, Damelia (LPPM UPMI, 2024)
Every company needs to pay attention to the people who work within the company so that it can continue to develop. This means that companies must treat employees well so that they can do their jobs effectively and efficiently. There are several different things that can influence how well someone does their job, such as how a company plans its employees, company culture, and the skills and abilities of each worker. So it is important to manage human resources so that they can carry out their duties well and productively. This research aims to find out how organizational culture and competence influence employee performance development with job satisfaction as a mediating variable. Qualitative methods were used in this research to explore the influence of organizational culture and competence on employee performance development with job satisfaction as a mediating variable. The technique used is simple random sampling. The research results show that organizational culture and competence influence employee performance development with job satisfaction as a mediating variable. In conclusion, organizational culture plays an important role in shaping individual performance and fostering a positive work environment.